A qualitative analysis of micro-credit group liability and women entrepreneurship's performance - Razli Che Razak; Isidore Ekpe; Norsiah Mat (2011)
Women entrepreneurs mostly do not have asset collaterals to secure loans in conventional commercial banks; and so they depend on micro-credit groups guarantee to secure loans from micro-finance banks in their localities. This is beneficial to the banks because it reduces their transaction cost as credit monitoring, supervision and enforcement is transferred to the credit groups. Group membership is also advantageous to an entrepreneur as it ensures easy access to new business ideas, information and resources for business performance. The effect of group liability on loan repayment has been measured in the literature and found to positive. However, the effect of group liability on members’ business performance has not received empirical attention in the literature. This is the focus of this study. The study adopted a qualitative method as a part of the authors’ full research methodology to support their quantitative results. The qualitative method involved in-depth interview to solicit responses from six women entrepreneurs who were members of credit groups of three micro-finance banks in Nigeria. It was discovered that women entrepreneurs who repaid their first loan cycle were not allowed by the banks to collect the next loan until all the members of their group have also completed the repayment of their loans. As such, those who repaid their loans early, especially the group leaders, had to wait for the rest of the members. This, according to the women, affected their business capital and slowed down their businesses. It was also discovered that if any group member could not repay her loan at maturity, all the group members were made to pay the outstanding amount. Though she would later refund the amount to the group, it was a kind of burden or tax to other members as well as a discouragement to hard work.